The The Influence of Selection and Job Placement on Employee Performance at PT. Bank Prisama Dana Tomohon Branch: The Influence of Selection and Job Placement on Employee Performance at PT. Bank Prisama Dana Tomohon Branch - Broto, Shalomitha (JURNAL ADMINISTRASI BISNIS, 2025)
Performance in this study is the achievement of work that has been completed optimally both in quality and quantity by an employee with the responsibilities that have been guven to him. The purpose of this study is to test and analyze the Influence of Selection and Job Placement on Employee Performance at PT. Bank Prisma Dana Tomohon Branch. The subjects in this study were 32 employee respondents at PT. Bank Prisma Dana Tomohon Branch. The analysis tool used in this study is Partial Least Square (PLS). The results of the study indicate that selection and job placement directly have a positive effect on employee performance. The results of this study are a scientific contribution, companies should always pay attention to selection and companies should consider job placement, so that it has a positive effect employee performance so that it is always consistent in the future. Contributions to further research and society.